Age-Related Transcriptional Deregulation of Genes Coding Synaptic Proteins in Alzheimer's Disease Murine Model: Potential Neuroprotective Effect of Fingolimod - Jęśko, Henryk; Wieczorek, Iga; Wencel, Przemysław Leonard; Gąssowska-Dobrowolska, Magdalena; Lukiw, Walter J.; Strosznajder, Robert Piotr (Frontiers in Molecular Neuroscience, 2021)
Alzheimer's disease (AD) induces time-dependent changes in sphingolipid metabolism, which may affect transcription regulation and neuronal phenotype. We, therefore, analyzed the influence of age, amyloid β precursor protein (AβPP), and the clinically approved, bioavailable sphingosine-1-phosphate receptor modulator fingolimod (FTY720) on the expression of synaptic proteins. RNA was isolated, reverse-transcribed, and subjected to real-time PCR. Expression of mutant (V717I) AβPP led to few changes at 3 months of age but reduced multiple mRNA coding for synaptic proteins in a 12-month-old mouse brain. Complexin 1 (Cplx1), SNAP25 (Snap25), syntaxin 1A (Stx1a), neurexin 1 (Nrxn1), neurofilament light (Nefl), and synaptotagmin 1 (Syt1) in the hippocampus, and VAMP1 (Vamp1) and neurexin 1 (Nrxn1) in the cortex were all significantly reduced in 12-month-old mice. Post mortem AD samples from the human hippocampus and cortex displayed lower expression of VAMP, synapsin, neurofilament light (NF-L) and synaptophysin. The potentially neuroprotective FTY720 reversed most AβPP-induced changes in gene expression (Cplx1, Stx1a, Snap25, and Nrxn1) in the 12-month-old hippocampus, which is thought to be most sensitive to early neurotoxic insults, but it only restored Vamp1 in the cortex and had no influence in 3-month-old brains. Further study may reveal the potential usefulness of FTY720 in the modulation of deregulated neuronal phenotype in AD brains.